Climate oscillations in the 20 000–11 000 cal BP range recorded in the Piaski and Szerokie Formations in the Bełchatów Opencast Lignite Mine: a look through radiocarbon date analysis - Michczyńska, Danuta J.; Wieczorek, Dariusz; Wachecka-Kotkowska, Lucyna; Krzyszkowski, Dariusz (Acta Geographica Lodziensia, 2022)
Radiocarbon dates of organic sediments, taken from the soil horizon, gyttja, peats, plant remains and mineral-organic sediments – silts and silty-sandy sediments with admixture of organic material – were collected and analysed. Age determinations were made for samples collected over a number of years from the upper part of sediments of the Piaski and Szerokie Formations in the Bełchatów Lignite Open Cast Mine (28 dates) and their surroundings (2 dates) (Fig. 1; Tab. 1). The organic sediments analysed are mainly associated with the valleys of the Krasówka, Struga Żłobnicka, Świętojanka and Widawka Rivers. They were formed within alluvia (probably fillings of oxbow lakes). Some of the organic deposits were formed in the vicinity of dunes or aeolian covers (mid-dune depressions). During the Late Glacial in this area, aggradation dominated the river valleys. Fluvial processes were accompanied by aeolian processes. A large proportion of aeolian grains is characteristic of the upper part of the profile of the sands formations. Despite the filling of the valleys with fluvio-aeolian sediments, fluvial erosion also occurred in places. The Folwark 1 and 2 sites in the Struga Żłobnicka River valley yielded 12 age determinations (from 14 810±170 to 11 130±120 BP, i.e. 18 270–12 900 cal BP). In the Widawka valley, the sites Bełchatów 3/88 BM, JG, I/83/JG, II/83/JG, Buczyna 8, Rogowiec 1 and Wola Grzymalina yielded 12 dates falling in the pe-riod 14 350±580 to 10 160±140 BP, i.e. 18 240––11 400 cal BP. In the Kleszczów 3/90 site, only one date of 11 460±120 BP (13 460–13 190 cal BP) related to peat in the Świętojanka River valley. The last two determinations, archived as site unknown and Kuców C–IIa, are dated 15 850±180 (19 360–18 930 cal BP) and 13 780±130 BP (16 950–16 520 cal BP). In the area of the present Szczerców field, the Parchliny-Chabielice site yielded three dates in the Krasówka River valley – 10 290±90 (12 450–11 830 cal BP), 11 840±110 BP (13 800–13 520 cal BP) and 15 440±160 (18 910–18 360 cal BP) (Tab. 1). Based on the collected dates, so-called PDF (Probability Density Functions) curves were drawn up in the range 20 000–11 000 cal BP (Fig. 3). The analysis used the shape analysis method of the summed probability density distributions of the calibrated radiocarbon dates (Fig. 3). The position of peaks of the obtained distributions on the time axis is in good agreement with the oxygen curve from the Greenland core NGRIP. There is a clear clustering of dates around the beginning of GI–1, but also around GI–1d, GI–1c2 and GI–1b. This was contributed to by the preferential sampling for dating from locations where changes in sediment lithology were evident (bottom and top of peat layer, soil on mineral deposits, bottom of oxbow fill, etc.). Therefore, the peaks of the obtained distributions should not be linked only to warm periods, but rather to transitions from cold to warm conditions or from warm to cold conditions. Although the dataset analysed is smallscale, the evident clustering of dates makes it possible to identify environmental responses to climate change over several time scales: - 19 500–18 900 cal BP (peak within GS–2b); - 17 800–17 300 cal BP (peak at transition GS––2b/GS–2a); - 16 800–16 600 cal BP (peak located at GS– –2a); - 15 200–14 300 cal BP (peak at GS–2a/GI–1e transition); - 14 100–13 800 cal BP (peak around GI–1d); - 13 600–13 550 cal BP (peak around GI–1c2); - 13 250–13 050 cal BP (peak around GI-1b); - 12 500–11 700 cal BP (peak around the second half of GS–1) The resolution of the analyses carried out does not make it possible to determine whether there were delays in the environmental response of the study area in relation to the changes recorded in the Greenlandic core, but any delays must be less than the average uncertainty of the radiocarbon dates analysed, i.e. 100 years. The analyses carried out used dates made using conventional techniques, which have relatively large uncertainties. It is probable that including new sites and precise 14C age determinations by the AMS technique would contribute to a higher resolution of this type of analysis.